New results and a model of scale effects on growth - Kul Bahadur Luintel; Panayiotis M. Pourpourides (Cardiff University, Cardiff Business School, 2022)
A consensus in the growth literature is that scale effects of R&D are non-existent across mature industrialized economies. However, the scrutiny across emerging economies is lacklustre at best. The empirical studies of scale effects also leave the issues of unbalanced regression (non-standard distribution) largely unaddressed. In this paper, we conduct separate but parallel empirical scrutiny of scale effects across the panels of industrialized and emerging countries, clearly addressing these econometric issues, and employing a more realistic measure of the scale of R&D activities than has been applied hitherto. We provide parallel but novel estimates of significant scale effects across emerging countries, and their absence across developed countries. We then propose an endogenous growth model and show that scale effects exist during growth transitions but not at the vicinity of the long-run equilibrium, which reconciles our results. Thus, we shed light on a long-debated and important issue. Estimates of our model's predictions reveal that the long-run growth rates of per capita real GDP and TFP are driven by the growth rates of technological innovation and aggregate employment, except that only the former matters for the TFP growth across emerging countries.
Keywords: O3; O4; O14; O33; O47; 330; Endogenous Technical Change; Scale Effects; Panel Integration and Cointegration